Short-term clinical and echocardiographic outcomes after use of polytetrafluoroethylene bicuspid pulmonary valve during the repair of tetralogy of Fallot - Prashant Ramdas Wankhade; Neeraj Aggarwal; Reena Khantwal Joshi; Mridul Agarwal; Raja Joshi; Ashwani Mehta; Sibashankar Kar (Wolters Kluwer Medknow Publications, 2019)
Background: Application of transannular patch (TAP) during the repair of tetralogy of Fallot (TOF) leads to the development of pulmonary regurgitation (PR). This PR is known to cause right ventricular (RV) volume overload and dysfunction which in turn leads to increase in both morbidity and mortality both in immediate and long-term periods. Here, we sought to analyze the effects of polytetrafluoroethylene (PTFE) pulmonary bicuspid valve on the early outcome of patients with TOF repair where TAP is needed. Subjects and Methods: This is a retroprospective, observational study where PTFE bicuspid pulmonary valve was incorporated in all consecutive patients undergoing repair of TOF involving the application of TAP. Postoperative inhospital course was assessed, and patients were followed till 6 months for the status of PR and peak RV outflow tract (RVOT) gradient. Results: 38 patients were enrolled in the study. The mean age of participants was 53.66 ± 78.67 months. Extubation in operating room was done in 31 (81.58%) patients. Duration of ventilator support was 10.48 ± 24.22 h, and duration of hospital stay was 7.95 ± 3.08 days. These data were compared with three recent studies where only TAP was applied. Extubation in operating room, mechanical ventilation time, and hospital stay were significantly improved in the present study. Out of 37 live patients, four (10.81%) patients had no PR, 28 (75%) had mild, 1 (2.7) had moderate, and 4 (10.81%) had severe PR. Average RVOT peak gradient was 18.8 ± 8.1 mmHg. Conclusion: Incorporation of PTFE bicuspid pulmonary valve during the repair of TOF appears to facilitate early extubation and thus reduces ventilator-associated comorbidities. Study needs further long-term follow-up to look for behavior of PTFE bicuspid valve.